St. Teresa of Jesus: The Woman Theologian - Berthold Anton Pareira (Studia Philosophica et Theologica, 2018)
Women have made very significant contribution to the transmission of faith and one of thegreatest figure in the history of this transmission is St.Teresa of Jesus, the woman theologian of the sixteenth century Spain. Her theology is a mystagogy of prayer, to the highest mystical union with God. It is a theology based on her experience and narrated in the first person singular. Her theology is a theology of humility. She is a woman of inquiry and of wonder. She wrote during a time of intense ecclesiastical scrutiny of texts. Kaum perempuan telah memberikan kontribusi yang sangat berarti bagi penerusan iman dan salah satu tokoh terbesar dalam sejarah penerusan iman ini adalah St.Teresa Yesus, teolog perempuan Spanyol abad keenam belas. Teologinya adalah suatu mistik doa, hingga persatuan mistik tertinggi dengan Tuhan. Ini adalah teologi berdasarkan pengalamannya sendiri dan dikisahkan dalam sudut pandang orang pertama tunggal. Teologinya adalah teologi kerendahan hati. Dia adalah wanita yang selalu ‘mencari’ dan bertanya penuh kagum. Dia menulis pada saat gereja melakukan pengawasan yang ketat terhadap tulisan rohani (pada saat pemeriksaan teks gerejawi yang intens).